2020
DOI: 10.1088/1361-6528/ab87cb
|View full text |Cite
|
Sign up to set email alerts
|

Aged sol-gel solution-processed texture tin oxide for high-efficient perovskite solar cells

Abstract: Mesoporous n–i–p perovskite solar cells (PeSCs) demonstrate attractive potential for obtaining high power conversion efficiencies (PCEs), by employing inorganic electron transport layers (ETLs). However, these ETLs composed of dual layers (a condense layer and a mesoporous layer) suffer the composite process and high sintering temperature. Here, we demonstrate a simple and efficient process to improve the device performance of PeSCs by using a textured SnO2 film. Self-aged sol-gel SnO2 solution after spin coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 56 publications
(74 reference statements)
0
1
0
Order By: Relevance
“…But the sol-gel SnO 2 lm suffered from poor interfacial contact electrical properties with the perovskite absorber layer because of the annealing effects, resulting in the degradation of performance of PSCs. 123 Wang et al reported a whole sol-gel crystallized SnO 2 fabrication process below 80 C (Fig. 4b).…”
Section: Solution-processable Methodsmentioning
confidence: 99%
“…But the sol-gel SnO 2 lm suffered from poor interfacial contact electrical properties with the perovskite absorber layer because of the annealing effects, resulting in the degradation of performance of PSCs. 123 Wang et al reported a whole sol-gel crystallized SnO 2 fabrication process below 80 C (Fig. 4b).…”
Section: Solution-processable Methodsmentioning
confidence: 99%